A NEW SPECIES OF FREYCINETIA (PANDANACEAE) FROM JAMBI, SUMATRA, INDONESIA - Elizabeth Anita Widjaja; Nursahara Pasaribu; Arief Hidayat (Reinwardtia, 2009)
WIDJAJA, E.A., PASARIBU, N., HIDAYAT, A. 2009. A new species Freycinetia (Pandanaceae) from Jambi, Sumatra, Indonesia. Reinwardtia 12 (5): 441–442. — Freycinetia berbakensis Widjaja, Pasaribu & Hidayat is proposed as a new species.